2017
DOI: 10.1186/s12940-017-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood mercury concentrations are associated with decline in liver function in an elderly population: a panel study

Abstract: Background: Mercury is a toxic heavy metal and is known to affect many diseases. However, few studies have examined the effects of mercury exposure on liver function in the general population. We examined the association between blood mercury concentrations and liver enzyme levels in the elderly. Methods: We included 560 elderly participants (60 years or older) who were recruited from 2008 to 2010 and followed up to 2014. Subjects visited a community welfare center and underwent a medical examination and measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 38 publications
(48 reference statements)
1
22
0
Order By: Relevance
“…In previous epidemiological studies, blood Hg showed a significant positive association with ALT in NHANES 2003-2004 [ 11 ], and with AST and ALT in KNHANES 2008-2012 [ 12 ]. A recent study [ 13 ] reported significantly higher AST levels in the highest quarter of blood Hg levels than in the lowest quarter, and the odds of high ALT levels (>35 IU/L) were 3.10 times higher in the highest quarter of blood Hg levels than in the lowest quarter in a repeated-measures study of Koreans over 60 years old. However, other studies have reported no association [ 9 , 10 ], and conflicting results have been reported depending on whether liver dysfunction was defined as a continuous or dichotomous variable within the same study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous epidemiological studies, blood Hg showed a significant positive association with ALT in NHANES 2003-2004 [ 11 ], and with AST and ALT in KNHANES 2008-2012 [ 12 ]. A recent study [ 13 ] reported significantly higher AST levels in the highest quarter of blood Hg levels than in the lowest quarter, and the odds of high ALT levels (>35 IU/L) were 3.10 times higher in the highest quarter of blood Hg levels than in the lowest quarter in a repeated-measures study of Koreans over 60 years old. However, other studies have reported no association [ 9 , 10 ], and conflicting results have been reported depending on whether liver dysfunction was defined as a continuous or dichotomous variable within the same study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 13 ] reported significantly higher AST levels in the highest quarter of blood Hg levels than in the lowest quarter, and the odds of high ALT levels (>35 IU/L) were 3.10 times higher in the highest quarter of blood Hg levels than in the lowest quarter in a repeated-measures study of Koreans over 60 years old. However, other studies have reported no association [ 9 , 10 ], and conflicting results have been reported depending on whether liver dysfunction was defined as a continuous or dichotomous variable within the same study [ 13 ]. Significantly higher GGT levels were found in the second-highest and highest quarters of blood Hg levels than in the lowest quarter [ 13 ], and the odds of high GGT (>47 IU/L for men and >21 IU/L for women) were 2.59 times higher for men and 2.03 times higher for women in the highest quarter of blood Hg levels than in the lowest quarter [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mercury primarily metabolized in the liver. Due to its accumulation in the liver, resultant severe hepatic damages 9 , including histopathological and ultrastructural lesions evidenced by periportal fatty degeneration and cell necrosis 10 , whereas, the kidney is the primary organ of elimination. Being recognized mercury as a hazardous environmental pollutant 11 , and has efficacy to produce several adverse effects on human health, achieve considerable attention and need to investigate through about the toxicity.…”
Section: Ijpsr (2018) Volume 9 Issue 3 (Research Article)mentioning
confidence: 99%